Proposal on the production process to finance companies sport from studying his followers - Cárdenas-Polanía, Wilson Andreas (Quality in Sport, 2015)
The follower of sport should be the focus of the operation of sport companies. For that we must understand their needs so we can develop the business model that gives direction to the sport company to achieve financial sustainability. The proposal is based on social psychology and sociology at the theoretical part and in two methodological research: A transversal cross-correlation descriptive and the other is based on statistical analysis of textual data. Taking some of its conclusions, the proposal aimed to channel the needs of the follower of sports to an exchange called cultural consumption. For this, the necessary elements that the company must develop to maximize emotions, motivations and identities during games, tournaments and sporting events. It does this using the amplification of symbolic values, develop statistics and promote the practice of sport. With this tour, arise actors that the process for its success must accompany: Athletes, media and advertisers. With these inputs we can make an intersection between the follower and the consumer of the sponsor.